2018
DOI: 10.1186/s12890-018-0711-8
|View full text |Cite|
|
Sign up to set email alerts
|

The long-term rate of change in lung function in urban professional firefighters: a systematic review

Abstract: BackgroundDespite the known occupational hazards, it is not yet clear whether long-term career firefighting leads to a greater rate of decline in lung function than would normally be expected, and how this rate of change is affected by firefighting exposures and other risk/protective factors.MethodsA systematic search of online electronic databases was conducted to identify longitudinal studies reporting on the rate of change in the forced expiratory volume in one second (FEV1) of forced vital capacity (FVC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 66 publications
4
34
1
1
Order By: Relevance
“…Acute airway inflammation has been documented 27. However, it remains unclear whether urban career firefighters without exposure to a non-routine disastrous event have an accelerated decline in pulmonary function 28. In our study, COPD mortality was significantly associated with cumulative fire-hours, after adjusting for employment duration.…”
Section: Discussionmentioning
confidence: 59%
“…Acute airway inflammation has been documented 27. However, it remains unclear whether urban career firefighters without exposure to a non-routine disastrous event have an accelerated decline in pulmonary function 28. In our study, COPD mortality was significantly associated with cumulative fire-hours, after adjusting for employment duration.…”
Section: Discussionmentioning
confidence: 59%
“…Heterogeneity and lack of excessive declines in pulmonary function in firefighters and associations with fire fighting duties have also been shown across cohorts. 14 , 27 , 34 , 35 Studies observing the Boston Fire Department from the late 1970s to the early 1980s found that firefighters who were not engaged in active firefighting duty also had large reductions in both FEV 1 and FVC, suggesting that other factors besides fire and smoke exposure promoted respiratory and pulmonary ailments. Additionally, these studies showed that firefighters who transitioned to less active assignments also had a greater decrement in ventilatory capacity than those who remained in fire-fighting positions.…”
Section: Discussionmentioning
confidence: 99%
“… 26 A systematic review of longitudinal changes in lung function among firefighters found non-smoking firefighters who routinely wore respiratory protection were more likely to have normal rates of decline in lung function. 27 Firefighters who reported “never or rarely” using their respiratory protection equipment during fire knockdown had a higher odds (odds ratio [OR]: 2.20; 95% confidence interval [CI]: 1.02 to 4.74) of accelerated FEV 1 decline (greater than 50 mL/yr) than those who “often or frequently” used their respiratory protection equipment. 40 The unprotected airway also provides an important exposure risk to carcinogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of the cumulative effects of firefighting on lung function has recently been published (3). It includes 22 studies whose findings are 'highly variable and provide an unclear picture of how the rate of change in lung function of firefighters relates to routine exposures; moreover the evidence for an 'exposure-response' relationship is not compelling'.…”
Section: Cardiorespiratory Diseasementioning
confidence: 99%